Modern Methods of Studying Terms in the Field of Pharmaceutics in English - Akhmedova Nargiza Alidjanovna (Genius Journals, 2022)
This article deals with an ESP course taught as an obligatory subject in a pharmacy undergraduate degree programme in Spain. The language course is only one of the contexts involving disciplinary English as the degree programme integrates English in several content subjects. The ESP course is an attempt to find the right balance between students’ language needs, pharmacy-specific language skills, and the language-related demands of pharmacy content subjects which integrate English. The co-existence of ESP and CLIL teaching is seen as an opportunity for a closer cooperation and coordination with disciplinary experts to make connections between disciplines and activities towards better learning outcomes. We propose a course aimed at raising students’ language awareness through focused tasks which will cater to student’s communicative needs related to the two main themes of the course: chemistry and pharmaceutical care
Keywords: Course design; university teaching; pharmacy; ESP